La Corroirie de la Chartreuse du Liget à Chemillé-sur-Indrois (Indre-et-Loire). Étude historique et architecturale - Bruno Dufaÿ (Revue Archéologique du Centre de la France)
Corroirie is a well-preserved medieval ensemble, which was the economic heart of the Chartreuse du Liget, near the town of Loches. Its buildings and its church have just been the subject of a building and historical study conducted by a multidisciplinary and multi-institutional team. It helped to trace the genesis and history of this place, from the modest establishment of the very end of the twelfth century. or the beginning of thirteenth century, until its transformation into a flour mill in the seventeenth century, with two water mills whose evolution could be traced in detail. Caught up in the turmoil of the Hundred Years War and the Wars of Religion, Corroirie was gradually strengthened to become, at the end of the sixteenth century, a real fortified house with moat, gatehouse, towers and arrow slits adapted for artillery. A lordship seat, it has the symbolic and functional attributes of a place of power, including a prison, a rare example of a building of this type in a monastic environment.